Molecular targets of fenofibrate in the cardiovascular-renal axis: A unifying perspective of its pleiotropic benefits. (June 2019) - Balakumar, Pitchai; Sambathkumar, Ramanathan; Mahadevan, Nanjaian; Muhsinah, Abdullatif Bin; Alsayari, Abdulrhman; Venkateswaramurthy, Nallasamy; Dhanaraj, Sokkalingam A.
Graphical abstract: Abstract: The activation of peroxisome proliferator-activated receptor α (PPARα) is a key pharmacological drug target for dyslipidemic management. Dyslipidemia is associated with abnormal serum lipid profiles viz. elevated total cholesterol, high triglyceride, elevated low-density lipoprotein cholesterol, and reduced high-density lipoprotein cholesterol levels. Fenofibrate, a third-generation fibric acid derivative, is an activator of PPARα indicated for the treatment of mixed dyslipidemia and hypertriglyceridemia in adults. Fenofibrate is considered an important lipid-lowering medication employed in patients afflicted with atherogenic dyslipidemia. Intriguingly, recent bench studies have demonstrated an array of cardiovascular and renal pleiotropic beneficial activities of fenofibrate, besides its foremost lipid-lowering action. The activation of PPARα by fenofibrate could negatively regulate the cardiomyocyte hypertrophy. In addition, fenofibrate has been suggested to have a protective effect against experimental ischemia/reperfusion injury in the myocardium in part via endoplasmic reticulum stress inhibition. Fenofibrate has also been shown to suppress arrhythmias in isolated rat hearts subjected to ischemic/reperfusion-induced cardiac injury. Moreover, in a rat model of metabolic syndrome and myocardial ischemia, fenofibrate therapy has been shown to restore antioxidant protection and improve myocardial insulin resistance. Furthermore, studies have highlighted the pleiotropic vascular endothelial protective and antihypertensive actions of fenofibrate. Interestingly, recent bench studies have demonstrated renoprotective actions of fenofibrate by implicating diverse mechanisms. This review sheds light on the current perspectives and molecular mechanistic aspects pertaining to the cardiovascular pleiotropic actions of fenofibrate. Additionally, the renal pleiotropic actions of fenofibrate by focusing its possible modulatory role on renal fibrosis, inflammation and renal epithelial-to-mesenchymal transition have been enlightened.